Statistik deskriptif pada persentase cakupan kepemilikan akta kelahiran pada penduduk 0-17 tahun menurut provinsi tahun 2020-2022 - Ulya, Diah Mariatul (Maliki Interdisciplinary Journal, 2025)
Displaying data has certainly become a part of everyday life. Whether in a formal or informal context, data collection requires a clear and less time-consuming way to decipher it. The science of statistics provides a solution to the complexity of data processing. Clear and precise presentation of data is an element of descriptive statistics. Descriptive statistics present information in various formats such as tables, graphs, or diagrams so that data sets can be easily understood. In descriptive statistics, measures of data centering include; mean, median, mode, range, variance, and standard deviation to provide a clear picture of data characteristics from 2020 to 2022. This report will explain about the data collection of “Descriptive Statistical Analysis on Percentage Coverage of Birth Certificate Ownership in Population 0-17 Years by Province 2020-2022” using Minitab program. The use of Minitab in the analysis plays a crucial role in obtaining valid and interpretative results. The output results obtained in the form of mean in 2020 is 87.69; in 2021 is 88.17; in 2022 is 89.97, median in 2020 is 90.83; in 2021 is 91.19; in 2022 is 92.56.